2015
DOI: 10.7717/peerj.1434
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics in benthic community composition and influencing factors in an upwelling-exposed coral reef on the Pacific coast of Costa Rica

Abstract: Seasonal upwelling at the northern Pacific coast of Costa Rica offers the opportunity to investigate the effects of pronounced changes in key water parameters on fine-scale dynamics of local coral reef communities. This study monitored benthic community composition at Matapalo reef (10.539°N, 85.766°W) by weekly observations of permanent benthic quadrats from April 2013 to April 2014. Monitoring was accompanied by surveys of herbivore abundance and biomass and measurements of water temperature and inorganic nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…Low seawater temperature, low dissolved oxygen concentration and enhanced nutrient concentrations provide evidence that several cold water intrusions (i.e. upwelling event) influenced the study site at Matapalo Reef during the period from December 2013 to April 2014 [ 23 , 24 ]. Data from Marina Papagayo (a field site within ~200 m distance to a coral reef) showed that increased intrusions of cold and nutrient-enriched subsurface water rised seawater p CO 2 , lowered pH and decreased Ω arag [ 37 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Low seawater temperature, low dissolved oxygen concentration and enhanced nutrient concentrations provide evidence that several cold water intrusions (i.e. upwelling event) influenced the study site at Matapalo Reef during the period from December 2013 to April 2014 [ 23 , 24 ]. Data from Marina Papagayo (a field site within ~200 m distance to a coral reef) showed that increased intrusions of cold and nutrient-enriched subsurface water rised seawater p CO 2 , lowered pH and decreased Ω arag [ 37 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The production of CaCO 3 by these organisms may be especially important for the reef´s CaCO 3 budget during periods with disruptive environmental events, when coral growth may cease (cf. Fig 7 , eutrophic condition; [ 24 ]). Interestingly, the observed loss in CaCO 3 substrate may explain the elevated pH and Ω arag at Matapalo Reef (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…palmata (the 14 most common stony coral species in Akumal Bay, as indicated by preliminary observations), or grouped as other stony coral species (identified using [ 54 ]). Macroalgae were identified as belonging to 4 growth forms: crustose coralline algae (CCA), erect calcified macroalgae (CMA), erect fleshy macroalgae (FMA), or turf algae [ 55 ]. Other sessile organisms were classified in 5 groups: gorgonians (including soft corals and sea fans), fire corals (defined as hydrocorals in the genus Millepora ), sponges, sea anemones, or zoanthids (zoantharians) [ 55 , 56 ].…”
Section: Methodsmentioning
confidence: 99%